2023
DOI: 10.3390/horticulturae9020252
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Rosemary (Rosmarinus officinalis, L.) Growth and Volatile Oil Constituents Grown under Soil Salinity Stress by Some Amino Acids

Abstract: The current study was carried out during the two consecutive winter seasons of 2019/2020 and 2020/2021 at the Experimental Farm of Ash-Shoubak University College, Jordan, as a pot experiment. This experiment was planned to evaluate the impact of various soil salinity levels (1.17, 3.34, 6.51, and 9.68 ds/m) and amino acid types (control, L-tryptophan acid at 100 ppm, glutamine acid at 200 ppm, and L-tryptophan acid + glutamine acid) as well as their combinations on growth, salt resistance index, and some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To mitigate the adverse effects of drought and salinity on aromatic plants and improve their productivity, it is crucial to understand the physiological and biochemical responses of aromatic plants under these conditions. Generally, the addition of salts to the soil solution limits the ability of the plant to absorb water, resulting in delayed growth and development [33]. The growth, yield, and quality of aromatic Lamiaceae plants can be adversely affected by salinity [34].…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the adverse effects of drought and salinity on aromatic plants and improve their productivity, it is crucial to understand the physiological and biochemical responses of aromatic plants under these conditions. Generally, the addition of salts to the soil solution limits the ability of the plant to absorb water, resulting in delayed growth and development [33]. The growth, yield, and quality of aromatic Lamiaceae plants can be adversely affected by salinity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Waly et al [47] investigated the effects of seaweed extract foliar application on rosemary using doses varying between 200 and 600 mL hL −1 and obtained plant height values which were similar to those found in the present study. Al-Fraihat et al [48] obtained rosemary plant heights of between 35 and 45 cm when applying different foliar amino acids. The foliar application of biostimulants allowed us to obtain a significant increase in the number and diameter of primary stems.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, its usage is supported and encouraged, and also, the academic community has focused on rosemary cultivation in recent years. Regarding biostimulant application on rosemary, the few studies conducted [46][47][48] have evaluated the effect of a single type of foliar biostimulant, and the information is very limited. On this basis, this study's objective was to evaluate the impact of four different biostimulants on the morphological and productive parameters of Rosmarinus officinalis L. organically cultivated in a Mediterranean environment without irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…This percentage was in line with data reported by Lamponi et al, from another Italian rosemary collected in Tuscany [ 40 ], but our yield was different from the data published by Jacotet-Navarro et al or by Nguyen-Kim et al, which reported extraction yields of around 25% and 33%, respectively, with 75% EtOH for S. rosmarinus collected in Morocco [ 47 ] and in Vietnam, respectively [ 52 ]. Since these authors used a conventional method of extraction, this difference may be ascribed to the environmental conditions, as the chemical composition of rosemary can be affected by soil properties [ 53 ], fertilizers [ 54 ], saltiness [ 55 ], humidity and temperature [ 56 ]. Furthermore, Balouiri et al, using a 22-h two-step maceration with hexane and methanol, were able to achieve an extraction yield of 15.8%, in line with our data, whereas, using an ultrasonic extraction, a yield of 8.7% was obtained [ 52 ].…”
Section: Discussionmentioning
confidence: 99%